Impact of low high-density lipoprotein-cholesterol level on 2-year clinical outcomes after acute myocardial infarction in patients with diabetes mellitus. Issue 1 (December 2016) - Joo, Hyung; Cho, Sang-A; Hong, Soon; Hur, Seung-Ho; Bae, Jang-Ho; Choi, Dong-Ju; Ahn, Young-Keun; Park, Jong-Seon; Choi, Rak-Kyeong; Choi, Donghoon; Kim, Joon-Hong; Han, Kyoo-Rok; et al.
Abstract Background It is still unclear whether low high-density lipoprotein cholesterol (HDL-C) affects cardiovascular outcomes after acute myocardial infarction (AMI), especially in patients with diabetes mellitus. Methods A total of 984 AMI patients with diabetes mellitus from the DIabetic Acute Myocardial InfarctiON Disease (DIAMOND) Korean multicenter registry were divided into two groups based on HDL-C level on admission: normal HDL-C group (HDL-C ≥ 40 mg/dL, n  = 519) and low HDL-C group (HDL-C < 40 mg/dL, n  = 465). The primary endpoint was 2-year major adverse cardiovascular events (MACE), defined as a composite of cardiac death, non-fatal myocardial infarction (MI), and target vessel revascularization (TVR). Results The median follow-up duration was 730 days. The 2-year MACE rates were significantly higher in the low HDL-C group than in the normal HDL-C group (MACE, 7.44% vs. 3.49%, p  = 0.006; cardiac death, 3.72% vs. 0.97%, p  = 0.004; non-fatal MI, 1.75% vs. 1.55%, p  = 0.806; TVR, 3.50% vs. 0.97%, p  = 0.007). Kaplan-Meier analysis revealed that the low HDL-C group had a significantly higher incidence of MACE compared to the normal HDL-C group (log-rankp  = 0.013). After adjusting for conventional risk factors, Cox proportional hazards analysis suggested that low HDL-C was an independent risk predictor for MACE (hazard ratio [HR] 3.075, 95% confidence interval [CI] 1.034-9.144, p  = 0.043). Conclusions In patients with diabetes mellitus, low HDL-C remained an independent risk predictor for MACE after adjusting for multiple risk factors during 2-year follow-up of AMI. Trial registration This study was the sub-analysis of the prospective multi-center registry of DIAMOND (Diabetic acute myocardial infarction Disease) in Korea. This is the observational study supported by Bayer HealthCare, Korea. Study number is 15614. First patient first visit was 02 April 2010 and last patient last visit was 09 December 2013.